Case Report: Successful surgical management of a challenging primary cardiac angiosarcoma - Li, Yichen; Ai, Yinze; Tang, Weijie; Liu, Jijia; Yang, Jinfu; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2023)
Primary cardiac tumors are exceptionally rare, with malignant tumor occurrences ranging from 0.0017% to 0.28%. Among these, primary cardiac angiosarcoma (PCA) stands as the most prevalent malignancy, primarily impacting the right cardiac system. In this case report, we present the instance of a 44-year-old woman who recently exhibited acute chest discomfort and was subsequently diagnosed with a microangiosarcoma within the right atrium and superior vena cava. Diagnostic modalities including chest x-rays, CT, MRI, and PET-CT were instrumental in pinpointing the tumor's location and nature. Surgical excision followed by pathological and immunological examinations confirmed the diagnosis. The patient's recovery post-surgery has been encouraging, with successful follow-up chemoradiotherapy administered. Despite advancements, devising optimal strategies for enhancing patient survival and quality of life in angiosarcoma cases remains a pressing research challenge.